Fluidity development of coking coal - Thomas, George (2022)
In most of the previous analytical studies on coking coal fluidity, single coal behaviour is well-documented but few studies have addressed coal blends regarding interactions in blends leading to possible non-additive behaviour. Many different techniques have been used to study single coals and blends, but of the two most promising are high temperature rheometry and 1H NMR. However, there is little work reported to date on using these techniques to study coal blends and this is the primary focus of this investigation.